A negative electrode material, a preparation method therefor, and an application thereof
Patent Information
- Application Number
- CN202511315578.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-09-15
AI Technical Summary
常规硬碳材料主要通过造孔提升平台区容量,导致材料充电能力较差材料;金属氧化物理论容量较高,但是在充放电过程中容易体积膨胀,造成循环能力差,因此,需要一种兼顾容量和快充的材料
(1)本发明的负极材料中,通过在BaCuO2基体材料的表面构建第一碳层(碳纳米管),有利于提高导电性,提高电子传输效率,其作为缓冲层可分散BaCuO2基体材料在循环过程中的应力,提高循环性能;第二碳层(硬碳材料)可以减缓BaCuO2在充放电过程中体积膨胀速度,从而提高材料的循环保持率,同时表面具有丰富的官能团及缺陷结构,储钠方式以表面容量控制为主,从而使材料表现出良好的动力学性能;本发明的负极材料通过各层的协调配合,具有高容量,优异的快充性能,结构稳定性、循环稳定性及倍率性能好。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of large battery technology, and more specifically, to a negative electrode material, its preparation method, and its application. Background Technology
[0002] In recent years, the electric vehicle industry has developed rapidly, and rechargeable batteries, as energy storage devices with high energy density, no memory effect, cleanliness, and recyclability, have been widely used in electric vehicles. The charging capacity and energy density of rechargeable batteries are among the key factors restricting the widespread adoption of electric vehicles. Conventional hard carbon materials mainly improve the capacity of the plateau region through pore formation, resulting in poor charging capacity. Metal oxides have higher theoretical capacity, but they are prone to volume expansion during charging and discharging, leading to poor cycle life. Therefore, a material that balances capacity and fast charging is needed.
[0003] In view of this, the present invention is hereby proposed. Summary of the Invention
[0004] One objective of this invention is to provide a negative electrode material with high capacity and fast charging performance, good structural stability, and excellent cycle performance and rate performance.
[0005] Another objective of this invention is to provide a method for preparing a negative electrode material that is simple and easy to implement, and the coordinated operation of each step can improve the structural stability and electrochemical performance of the negative electrode material.
[0006] Another object of the present invention is to provide a negative electrode.
[0007] Another object of the present invention is to provide a battery.
[0008] Another object of the present invention is to provide an electrical device.
[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A negative electrode material includes a negative electrode substrate, a first carbon layer, and a second carbon layer, wherein the first carbon layer is located on the surface of the negative electrode substrate, and the second carbon layer is located on the surface of the first carbon layer; the negative electrode substrate includes BaCuO2; the first carbon layer includes carbon nanotubes; and the second carbon layer includes a hard carbon material.
[0010] In some embodiments, the D50 particle size of the BaCuO2 is 10~15nm.
[0011] In some embodiments, the thickness of the second carbon layer is 1~5 nm.
[0012] In some embodiments, the sodium battery prepared from the negative electrode material has a capacity greater than 400 mAh / g at 0.1C.
[0013] In some embodiments, the sodium battery prepared from the negative electrode material retains more than 73% of its capacity at 0.1C and 500 cycles.
[0014] In some embodiments, the sodium battery prepared from the negative electrode material retains more than 82% of its capacity at 2C.
[0015] The method for preparing the negative electrode material as described above includes the following steps: Copper malate, barium ethylenediaminetetraacetate, solvent, and binder are first mixed and first dried to obtain a first material; the first material is second mixed with carbon nanotubes and alcohol solvent and second dried to obtain a second material; a diluted asphalt solution is third mixed with the second material to obtain a mixed system; the mixed system is subjected to a hydrothermal reaction, the solids are collected, and then subjected to a third drying and carbonization treatment.
[0016] In some embodiments, the mass ratio of copper malate, barium ethylenediaminetetraacetate, carbon nanotubes and pitch is 1:2.2:(0.0005~0.008):(5~10).
[0017] In some embodiments, the adhesive material includes at least one of polyvinyl alcohol, polyethylene glycol, polypropylene glycol, and sodium carboxymethyl cellulose.
[0018] In some embodiments, the asphalt diluent comprises asphalt and light oil, wherein the mass ratio of the asphalt to the light oil is (1~3):1.
[0019] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes.
[0020] In some embodiments, the mass ratio of the carbon nanotubes to the alcohol solvent is 1:(14~20).
[0021] In some embodiments, the first mixing specifically includes: mixing and stirring the copper malate, the barium ethylenediaminetetraacetate, and the solvent, and then mixing them with the binder material.
[0022] In some embodiments, the first drying is freeze drying, and the freeze drying temperature is -20 to -40°C.
[0023] In some embodiments, the temperature of the second drying is 80~120°C.
[0024] In some embodiments, the temperature of the hydrothermal reaction is 180~220°C, and the time of the hydrothermal reaction is 2~6 hours.
[0025] In some embodiments, the third drying is freeze drying, and the freeze drying temperature is -20 to -40°C.
[0026] In some embodiments, the carbonization temperature is 1000~1400℃, and the carbonization time is 4~8h.
[0027] In some embodiments, the carbonized material is cooled.
[0028] A negative electrode sheet comprising the aforementioned negative electrode material, or a negative electrode material obtained by the method described above.
[0029] A sodium battery, comprising the aforementioned negative electrode.
[0030] An electrical device comprising the aforementioned sodium battery.
[0031] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) In the negative electrode material of the present invention, by constructing a first carbon layer (carbon nanotube) on the surface of the BaCuO2 matrix material, it is beneficial to improve conductivity and electron transport efficiency. As a buffer layer, it can disperse the stress of the BaCuO2 matrix material during cycling and improve cycle performance. The second carbon layer (hard carbon material) can slow down the volume expansion rate of BaCuO2 during charging and discharging, thereby improving the cycle retention rate of the material. At the same time, the surface has abundant functional groups and defect structures, and the sodium storage mode is mainly controlled by surface capacity, so that the material exhibits good kinetic performance. The negative electrode material of the present invention has high capacity, excellent fast charging performance, good structural stability, cycle stability and rate performance through the coordinated cooperation of each layer.
[0032] (2) The method for preparing the negative electrode material of the present invention involves using copper malate, barium ethylenediaminetetraacetate, solvent, and binder to obtain a porous gel, and obtaining a first material through a first drying process; mixing the first material with carbon nanotubes and an alcohol solvent to construct a porous carbon nanotube conductive network; mixing a diluted asphalt solution with a second material, and under hydrothermal conditions, the asphalt undergoes preliminary cross-linking and curing; in the carbonization stage, copper ions in copper malate act as a catalyst to promote the carbonization reaction of the asphalt, and copper and barium ions preferentially accumulate in the core region of the material to form BaCuO2 cores, while copper malate... The malate and barium ethylenediaminetetraacetate ions interact with pitch through hydrogen bonds and van der Waals forces, forming a carbon layer structure on the surface of the carbon nanotube-coated BaCuO2. Furthermore, at high temperatures, copper malate decomposes to produce small molecules of H2O, NH3, and CO2, which form a porous structure on the hard carbon during release, increasing the contact area of the electrolyte material and improving the ion diffusion rate. The BaCuO2 coating on carbon nanotubes further enhances electronic conductivity, and BaCuO2 can undergo an alloying reaction with sodium, increasing the capacity of the anode material. The anode material obtained through the above steps exhibits excellent structural stability, cycle performance, and rate performance.
[0033] (3) The sodium battery of the present invention has excellent structural stability, cycle performance and rate performance, and high safety performance. Detailed Implementation
[0034] The embodiments of the present invention will be described in detail below with reference to examples. However, those skilled in the art will understand that the following examples are for illustrative purposes only and should not be considered as limiting the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer are followed. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.
[0035] According to one aspect of the present invention, the present invention relates to a negative electrode material, comprising a negative electrode substrate, a first carbon layer and a second carbon layer, wherein the first carbon layer is located on the surface of the negative electrode substrate and the second carbon layer is located on the surface of the first carbon layer; the negative electrode substrate comprises BaCuO2; the first carbon layer comprises carbon nanotubes; and the second carbon layer comprises a hard carbon material.
[0036] In the anode material of this invention, the construction of a first carbon layer (carbon nanotubes) on the surface of the BaCuO2 matrix material improves conductivity and electron transport efficiency. As a buffer layer, it can disperse the stress of the BaCuO2 matrix material during cycling, thus improving cycle performance. The second carbon layer (hard carbon material) can slow down the volume expansion rate of BaCuO2 during charging and discharging, thereby improving the cycle retention rate of the material. At the same time, the surface has abundant functional groups and defect structures, and the sodium storage mode is mainly controlled by surface capacity, thus giving the material good kinetic performance. The anode material of this invention has a core-shell structure, and through the coordinated cooperation of each layer, it has high capacity, excellent fast charging performance, good structural stability, cycle stability, and rate performance.
[0037] In some embodiments, the D50 particle size of the BaCuO2 is 10-15 nm, such as 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, or 15 nm. The BaCuO2 of the present invention has a suitable D50 particle size, which can shorten the diffusion path of sodium ions and improve the capacity and rate performance of the anode material.
[0038] In some embodiments, the thickness of the second carbon layer is 1-5 nm, such as 2 nm, 3 nm, 4 nm, or 5 nm. The second carbon layer of this invention has a suitable thickness, which ensures excellent electronic-ionic conductivity of the anode material. If the thickness of the second carbon layer is too low, the effect of suppressing volume expansion is poor; if the thickness of the second carbon layer is too high, it is detrimental to capacity utilization.
[0039] In some embodiments, the sodium battery prepared from the negative electrode material has a capacity greater than 400 mAh / g at 0.1C, such as 405 mAh / g, 410 mAh / g, 420 mAh / g, 440 mAh / g, 450 mAh / g, 470 mAh / g, etc. In some embodiments, the sodium battery prepared from the negative electrode material retains a capacity of greater than 73% at 0.1C after 500 cycles, such as 74%, 78%, 80%, 85%, 90%, etc. In some embodiments, the sodium battery prepared from the negative electrode material retains a capacity of greater than 82% at 2C, such as 85%, 88%, 90%, 92%, etc. The sodium battery prepared from the negative electrode material of the present invention has high capacity, high capacity retention, and good cycle performance and rate performance.
[0040] In some embodiments, the coating thickness test includes: cutting particles with an argon ion beam and observing the cut surface using a transmission electron microscope to determine the coating thickness based on different crystal structures. According to another aspect of the invention, the invention also relates to a method for preparing the negative electrode material as described above, comprising the following steps: Copper malate, barium ethylenediaminetetraacetate, solvent, and binder are first mixed and first dried to obtain a first material; the first material is second mixed with carbon nanotubes and alcohol solvent and second dried to obtain a second material; a diluted asphalt solution is third mixed with the second material to obtain a mixed system; the mixed system is subjected to a hydrothermal reaction, the solids are collected, and then subjected to a third drying and carbonization treatment.
[0041] The method for preparing the negative electrode material of the present invention involves obtaining a porous gel using copper malate, barium ethylenediaminetetraacetate, a solvent, and a binder, followed by a first drying process to obtain a first material. The first material is then mixed with carbon nanotubes and an alcohol solvent to construct a porous carbon nanotube conductive network. A diluted asphalt solution is mixed with a second material, and under hydrothermal conditions, the asphalt undergoes preliminary cross-linking and curing. During the carbonization stage, copper ions in copper malate act as a catalyst to promote the carbonization reaction of the asphalt. Copper and barium ions preferentially accumulate in the core region of the material to form BaCuO2 nuclei. The EDTA ions of fructate and barium ethylenediaminetetraacetate interact with pitch through hydrogen bonds and van der Waals forces, forming a carbon layer structure on the surface of the carbon nanotube-coated BaCuO2. Furthermore, at high temperatures, copper malate decomposes to produce small molecules of H2O, NH3, and CO2, which form a porous structure on the hard carbon during release, increasing the contact area of the electrolyte material and improving the ion diffusion rate. The BaCuO2 coating on carbon nanotubes further enhances electronic conductivity, and BaCuO2 can undergo an alloying reaction with sodium, increasing the capacity of the anode material. The anode material obtained by this invention through the above steps exhibits excellent structural stability, cycle performance, and rate performance. This method is simple to operate and conducive to industrialization.
[0042] In some embodiments, the mass ratio of copper malate, barium ethylenediaminetetraacetate, carbon nanotubes, and asphalt is 1:2.2:(0.0005~0.008):(5~10), for example, 1:2.2:0.001:5, 1:2.2:0.005:7, 1:2.2:0.007:6, 1:2.2:0.008:10, etc. The copper malate, barium ethylenediaminetetraacetate, carbon nanotubes, and asphalt of the present invention have a suitable mass ratio, which can ensure the coating effect of the first carbon layer and the second carbon layer, allowing the three to better exert their synergistic effect.
[0043] In some embodiments, the binder material includes at least one selected from polyvinyl alcohol, polyethylene glycol, polypropylene glycol, and sodium carboxymethyl cellulose, such as a combination of polyvinyl alcohol and polyethylene glycol, a combination of polyethylene glycol and polypropylene glycol, or a combination of polypropylene glycol and sodium carboxymethyl cellulose. The present invention utilizes the above-mentioned binder material to form an organic template for a superior gel with copper malate and barium ethylenediaminetetraacetate, thereby forming a porous BaCuO2.
[0044] In some embodiments, the asphalt diluent comprises asphalt and light oil, wherein the mass ratio of asphalt to light oil is (1~3):1, for example, 1:1, 1.5:1, 2:1, 3:1, etc. The light oil of this invention is composed of hydrocarbons such as alkanes, alkenes, and aromatics, and may also contain small amounts of sulfur-, nitrogen-, and oxygen-containing compounds, serving as a diluent for the asphalt. A suitable ratio of asphalt to light oil is beneficial for ensuring the dilution effect of the asphalt.
[0045] In some embodiments, the carbon nanotubes include single-walled carbon nanotubes.
[0046] In some embodiments, the mass ratio of the carbon nanotubes to the alcohol solvent is 1:(14~20), for example, 1:14, 1:15, 1:18, or 1:20. In some embodiments, the alcohol solvent includes at least one selected from polyvinyl alcohol, polyethylene glycol, methanol, and propanol.
[0047] In some embodiments, the first mixing specifically includes: mixing and stirring the copper malate, the barium ethylenediaminetetraacetate, and the solvent, and then mixing them with the binder material; the above-mentioned order of addition helps to ensure the performance of the first material.
[0048] In some embodiments, the first drying is freeze-drying, and the freeze-drying temperature is -20 to -40°C, for example -20°C, -25°C, -30°C, -40°C, etc. This invention employs suitable freeze-drying to ensure the drying effect.
[0049] In some embodiments, the temperature of the second drying is 80~120°C. The present invention uses a suitable second drying method to ensure the physical and chemical properties of the second material.
[0050] In some embodiments, the temperature of the hydrothermal reaction is 180~220℃, for example 180℃, 190℃, 200℃, 300℃, etc.; the time of the hydrothermal reaction is 2~6h, for example 2h, 3h, 4h, 5h, or 6h, etc. The present invention uses suitable hydrothermal reaction conditions to ensure that the materials undergo a full reaction.
[0051] In some embodiments, the third drying method is freeze drying, and the freeze drying temperature is -20 to -40°C, for example -20°C, -25°C, -30°C, -40°C, etc. The present invention employs a suitable third drying method to ensure the performance of the second material.
[0052] In some embodiments, the carbonization temperature is 1000~1400℃, such as 1000℃, 1100℃, 1150℃, 1200℃, 1300℃, 1400℃, etc. In some embodiments, the carbonization time is 4~8 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, etc. In some embodiments, carbonization is carried out in an inert atmosphere, such as nitrogen or helium. In some embodiments, the heating rate is 3~8℃ / min, such as 3℃ / min, 4℃ / min, 5℃ / min, or 8℃ / min, etc. This invention employs suitable carbonization conditions to ensure the carbonization effect, thereby forming a negative electrode material with a suitable structure and coating layer, ensuring the structural stability and electrochemical performance of the negative electrode material.
[0053] In some embodiments, the carbonized material is cooled to room temperature.
[0054] According to another aspect of the invention, the invention also relates to a negative electrode sheet comprising the aforementioned negative electrode material, or a negative electrode material obtained by the method.
[0055] The negative electrode of this invention has excellent structural stability and good electrochemical performance.
[0056] According to another aspect of the invention, the invention also relates to a sodium battery comprising the aforementioned negative electrode.
[0057] The sodium battery of the present invention has excellent structural stability, cycle performance and rate performance, and high safety performance.
[0058] According to another aspect of the invention, the invention also relates to an electrical device including the aforementioned sodium battery. The electrical devices of the invention include electric vehicles, power tools, etc.
[0059] The following explanation, combined with specific embodiments and comparative examples, further illustrates the point.
[0060] Example 1 A method for preparing a negative electrode material includes the following steps: (1) Add 10g of copper malate and 22g of barium ethylenediaminetetraacetate to 100g of water and stir until completely dissolved to obtain the first solution.
[0061] (2) Add 5g of polyvinyl alcohol to the first solution above, mix evenly, and freeze dry to obtain the first material.
[0062] (3) The first material above is ultrasonically mixed with 0.05g of single-walled carbon nanotubes and 100mL of ethanol and dried to obtain the second material.
[0063] (4) Add 70g of asphalt to 200mL of light oil to form a mixture.
[0064] (5) Add the second material to the mixture to obtain a mixed system.
[0065] (6) Pour the above mixture into a hydrothermal reactor and carry out a hydrothermal reaction at 200°C for 5 hours. Then freeze-dry the hydrothermal reaction product at -20°C.
[0066] (7) The dried material is subjected to carbonization treatment at a heating rate of 5℃ / min, heated to 1200℃, and held for 6 hours. After cooling, the negative electrode material can be obtained.
[0067] Example 2 A method for preparing a negative electrode material differs from that in Example 1 in that: The mass of the asphalt in step (4) is 50g.
[0068] Example 3 A method for preparing a negative electrode material differs from that in Example 1 in that: The mass of the asphalt in step (4) is 60g.
[0069] Example 4 A method for preparing a negative electrode material differs from that in Example 1 in that: The mass of the asphalt in step (4) is 85g.
[0070] Example 5 A method for preparing a negative electrode material differs from that in Example 1 in that: The mass of the asphalt in step (4) is 100g.
[0071] Example 6 A method for preparing a negative electrode material differs from that in Example 1 in that: In step (7), the carbonization temperature is 700℃.
[0072] Example 7 A method for preparing a negative electrode material differs from that in Example 1 in that: In step (7), the carbonization temperature is 1400℃.
[0073] Example 8 A method for preparing a negative electrode material differs from that in Example 1 in that: In step (3), the mass of the single-walled carbon nanotube is 0.007 g.
[0074] Example 9 A method for preparing a negative electrode material differs from that in Example 1 in that: In step (3), the mass of the single-walled carbon nanotube is 0.08 g.
[0075] Comparative Example 1 A method for preparing a negative electrode material differs from that in Example 1 in that: Step (3) does not include ethanol, meaning that the single-walled carbon nanotubes are directly mixed with asphalt without ultrasonic dispersion, resulting in a mixed system.
[0076] Comparative Example 2 A method for preparing a negative electrode material differs from that in Example 1 in that: In step (4), no light oil is added. The second material is directly mixed with asphalt to obtain a mixed system.
[0077] Experimental Example Batteries were prepared by using the negative electrode materials of each embodiment and comparative example, including the following steps: Using the negative electrode materials prepared in the above embodiments and comparative examples as negative electrodes, a slurry was made with conductive carbon black and binder at a mass ratio of 8:1:1. The slurry was then uniformly coated on aluminum foil and dried in a forced-air oven to form a negative electrode sheet. A sodium sheet was used as the counter electrode. A 1.0 mol / L NaFPO6 mixed organic solution (solvents were EC and DEC, with a volume ratio of 1:1) and a glass fiber membrane were used as the separator to prepare a CR2032 coin cell.
[0078] Electrochemical performance tests were conducted at a current density of 0.1C, including capacity, capacity retention after 500 cycles, and capacity retention at 2C.
[0079] The test results are shown in Table 1.
[0080] Table 1 Test Results
[0081] As shown in Table 1, the preparation method of the negative electrode material of the present invention, through the coordination of each step, results in a second carbon layer with a suitable thickness, and the battery prepared by the negative electrode material has high capacity, excellent capacity retention rate and rate performance.
[0082] Specifically, as shown in Examples 1-5, with the increase of asphalt addition, the thickness of the second carbon layer gradually increases, the capacity of the carbon-coated material gradually decreases, the capacity retention rate gradually increases, and the rate performance also shows a trend of first increasing and then decreasing. This is because the sodium storage capacity of carbon is lower than that of BaCuO2. Increasing the thickness of the carbon layer will gradually reduce the specific capacity of the material. BaCuO2 undergoes severe volume expansion during sodium storage. With the increase of cycle number, the material structure is irreversibly damaged, and the capacity will decrease significantly. After carbon coating, the outer carbon layer can slow down the volume expansion rate of the material during charging and discharging, thereby improving the cycle retention rate of the material. At the same time, the surface has abundant functional groups and defect structures, and the sodium storage method is mainly controlled by surface capacity, thus making the material exhibit good kinetic performance.
[0083] As can be seen from Examples 1 and 6-7, as the carbonization temperature increases, on the one hand, the coating thickness of the second carbon layer decreases and the material capacity gradually increases; on the other hand, the order of the second carbon layer increases, the capacity retention rate improves, and the kinetic performance slightly decreases.
[0084] As can be seen from Examples 1 and 8-9, with the increase of carbon nanotube addition, the material capacity and cycle retention remain basically unchanged, and the kinetics remain almost unchanged after a significant increase. This is because the addition of carbon nanotubes increases the electronic conductivity of the material and improves the kinetics. However, when the addition amount reaches a certain level, electronic conductivity is not the key factor restricting the improvement of kinetics, so the kinetics will not be significantly improved.
[0085] As shown in Example 1 and Comparative Example 1, when single-walled carbon nanotubes are directly mixed with asphalt without ultrasonic dispersion, the carbon nanotubes cannot be uniformly coated on BaCuO2, affecting the electronic conductivity of the material and resulting in poor kinetics. As shown in Example 1 and Comparative Example 2, without the addition of light oil, the asphalt cannot form a uniform coating layer on the particle surface, leading to excessively rapid local expansion and thus affecting cycle stability.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A negative electrode material, characterized in that, It includes a negative electrode substrate, a first carbon layer and a second carbon layer, wherein the first carbon layer is located on the surface of the negative electrode substrate and the second carbon layer is located on the surface of the first carbon layer; the negative electrode substrate includes BaCuO2; the first carbon layer includes carbon nanotubes; and the second carbon layer includes hard carbon material.
2. The negative electrode material according to claim 1, characterized in that, The D50 particle size of the BaCuO2 is 10~15nm.
3. The negative electrode material according to claim 1, characterized in that, The thickness of the second carbon layer is 1~5 nm.
4. The negative electrode material according to claim 1, characterized in that, It includes at least one of the following features (1) to (3): (1) The sodium battery prepared by the negative electrode material has a capacity greater than 400 mAh / g at 0.1C; (2) The sodium battery prepared from the negative electrode material retains a capacity of more than 73% at 0.1C and 500 cycles; (3) The sodium battery prepared by the negative electrode material has a capacity retention rate of more than 82% at 2C.
5. The method for preparing the negative electrode material according to any one of claims 1 to 4, characterized in that, Includes the following steps: Copper malate, barium ethylenediaminetetraacetate, solvent and binder are first mixed and first dried to obtain the first material; The first material is mixed with carbon nanotubes and an alcohol solvent in a second process and then dried in a second process to obtain the second material. The diluted asphalt is mixed with the second material in a third process to obtain a mixed system; The mixture is subjected to a hydrothermal reaction, the solids are collected and subjected to a third drying and carbonization treatment.
6. The method for preparing the negative electrode material according to claim 5, characterized in that, It includes at least one of the following features (1) to (5): (1) The mass ratio of copper malate, barium ethylenediaminetetraacetate, carbon nanotubes and asphalt is 1:2.2:(0.0005~0.008):(5~10); (2) The adhesive material includes at least one of polyvinyl alcohol, polyethylene glycol, polypropylene glycol and sodium carboxymethyl cellulose; (3) The asphalt diluent includes asphalt and light oil, and the mass ratio of the asphalt to the light oil is (1~3):1; (4) The carbon nanotubes include single-walled carbon nanotubes; (5) The mass ratio of the carbon nanotubes to the alcohol solvent is 1:(14~20).
7. The method for preparing the negative electrode material according to claim 5, characterized in that, It includes at least one of the following features (1) to (7): (1) The first mixing specifically includes: mixing and stirring the copper malate, the barium ethylenediaminetetraacetate and the solvent, and then mixing them with the adhesive material; (2) The first drying is freeze drying, and the freeze drying temperature is -20~-40℃; (3) The temperature of the second drying process is 80~120℃; (4) The temperature of the hydrothermal reaction is 180~220℃, and the time of the hydrothermal reaction is 2~6h; (5) The third drying process is freeze drying, and the freeze drying temperature is -20~-40℃; (6) The carbonization temperature is 1000~1400℃ and the carbonization time is 4~8h; (7) Cool the carbonized material.
8. A negative electrode sheet, characterized in that, It includes the negative electrode material according to any one of claims 1 to 4, or the negative electrode material obtained by the method according to any one of claims 5 to 7.
9. A sodium battery, characterized in that, Includes the negative electrode sheet as described in claim 8.
10. An electrical appliance, characterized in that, Including the sodium battery as described in claim 9.
Citation Information
Patent Citations
Fuel cell system including dense oxygen barrier layer
CN107980186A
Variable capacitor and associated fabrication method
CN1408120A